Daily soil temperature and moisture records (2018-2019) from observation site GEC-1801 in the Argentinian Andes - Carla Tapia Baldis; Martín Mendoza López; Dario Trombotto Liaudat; Noelia Sileo (PANGAEA, 2022)
Soil temperature (°C) and water saturation (%) were collected in the uppermost levels of the active layer from “El Candidato” rock glacier, from 2018 to 2019. “El Candidato” is an active rock glacier placed in the Argentinian Central Andes at 4012 m.a.s.l. (31.898672°S; 70.178486°W). The purpose of the data set was to analyze the volumetric water content and ground temperature variation in the landform frontal talus, in terms of active layer depth estimation. Four investigation depths were selected: 5 cm, 25 cm, 50 cm and 70 cm. Lectures were made 6 times a day, at 02:00, 06:00, 10:00, 14:00, 18:00 and 22:00 hours (GMT-3), from 17/04/2018 to 26/03/2019 with 4 SMT-100 data loggers (TRUEBNER GmbH, Germany). Soil temperature and water saturation were calculated as the average of the six daily data, considering for the last one site-specific porosity estimations.